The use of aspartame as sweetener and sorbitol as bulking agent for dehydrated pineapple - Cunanan, Cherry Lou Pachoco (1998)
ABSTRACT The country's surplus in raw materials and diet enthusiasts' search for low-calorie foods led to this study on the use of aspartame as alternative sweetener and sorbitol as bulking agent in the production of dehydrated pineapple. Aspartame was used as a sugar substitute, providing sweetness but not bulk due to minimal usage. Sorbitol, a bulking agent, provided water binding property that aspartame lacks. The best levels of sorbitol and aspartame were determined to be 14% and 12% respectively, based on overall acceptability scores of dehydrated pineapple samples. The sorbitol- and aspartame-treated dehydrated pineapple was produced thrice at bench scale and was found to be reproducible. Production scale was increased from bench to pilot scale and the properties of the products from the two levels were not significantly different. The caloric content of the sorbitol- and aspartame-treated product is 55.41 kcal per 100 g whereas that of the sugar-treated one is 183.00 kcal per 100 g. Microbial analysis of the sorbitol- and aspartame-treated dehydrated pineapple samples showed mold growth possibly due to the pre and post treatments that the pineapples had undergone and to the substantial numbers of microorganisms present in the atmosphere. Cost analysis of the samples showed that the selling price for the sorbitol- and aspartame-treated product is P14.86 per 100 grams while the sugar-treated dehydrated pineapple costs P13.62 per 100 g.